TR SANDAH: WITHERING JUDICIAL ACTIVISM (UUM Journal of Legal Studies, 2024)
This study discusses the Federal Court judgment in the case of Director of Forest, Sarawak & Anor v. TR Sandah Tabau & Ors and other appeals [2017] 3 CLJ 1. The Federal Court’s decision was said to deviate from an earlier established principle of the common law recognition of existing indigenous peoples’ land rights, the content and extent of which are determined by community customary laws. The common law acknowledgement or recognition of indigenous peoples’ pre-existing rights to their traditional and customary lands held by the Federal Court in Adong bin Kuwau v Kerajaan Negeri Johor [1997] 1 MLJ 418 and Madeli Salleh v. Superintendent of Lands & Surveys & Anor [2005] 3 CLJ 697 complimented the existing safeguards given under the Federal Constitution and statutory laws relevant to Orang Asli in Peninsular Malaysia and the natives of Sabah and Sarawak. Therefore, this study aims to examine whether the Federal Court’s decision in TR Sandah FC reflects judicial conservatism by giving preference to statutory laws passed by the elected officials that resulted in the regression of the recognition of the indigenous peoples’ customary land rights. The method adopted in this study is a qualitative approach via doctrinal legal research. This is a text-based examination of legal texts and other scholarly materials. This shows judges in Malaysia are said to play a more conservative role in the interpretation of legislation. It would be fundamental to highlight the development of the judicial treatment of the indigenous peoples’ land rights in Malaysia and its implications.